REINTERPRETASI HADIS-HADIS KEPEMIMPINAN - Hasanuddin Hasanuddin (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2021)
This article discusses the reinterpretation of leadership hadiths which consist of four hadiths as the main hadiths. First, the hadith prohibits someone from asking to be appointed as a leader. Second, the hadith about the obligation of leadership to the Quraysh. Third, the hadith about female leaders will not be successful. Fourth, the hadith about the person most entitled to become a leader is the most qari/expert of fiqh. In this paper, the hadiths will be discussed one by one including the matan, the interpretation of the hadith, and the meaning of the hadith. Then the hadith is understood contextually but still in the maqashid shari'ah corridor. The results of this study indicate that these hadiths are not mutawatir hadiths and are not related to matters of faith and worship, so that conducting further research with reinterpretation is a necessity.